PILGRIMAGE TOURISM EVENTS IN INDONESIA: EXAMINING THE RELATIONSHIP OF BEHAVIORAL BELIEF, MOTIVATION TO COMPLY, ATTITUDES, SUBJECTIVE NORMS, AND INTENTION TO PARTAKE - Indrianto, Agoes Tinus Lis; Oktavio, Adrie; Nugroho, Agustinus (Jurnal Aplikasi Manajemen, 2022)
For decades, the close link between pilgrims and tourists has been recognized by medieval scholars and tourism historians and has been the subject of further research in recent years. Pilgrimage has become a phenomenal thing and is growing quite rapidly because it is considered a crucial factor for many adherents of several major religions in the world. Pilgrimage and tourism have a very close relationship. This quantitative study investigates predictors of intention to partake in pilgrimage events in Indonesia. This study adopts the purposive sampling technique in collecting data from the respondents. A total of 189 respondents participated in filling out the online questionnaire. The findings of this study indicate that the four hypotheses proposed in this study are not entirely acceptable. Attitudes do not significantly affect the intention to partake in pilgrimage events. Behavioral beliefs on attitudes, motivation to comply with subjective norms, and subjective norms on intentions to partake in pilgrimage events are three hypotheses that have significant influence. Several recommendations for future research are also outlined at the end of this study. One of them recommends exploring more predictors to identify the intention to partake in pilgrimage events as a big potential to develop pilgrimage tourism in Indonesia further.